Method for producing lithium metal composite oxide and pressed powder body

JP2025022408APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023126946
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、微粒子が少なく、結晶性が高いリチウム金属複合酸化物を高い生産効率で製造できるリチウム金属複合酸化物の製造方法、及びこの製造方法に用いることができる圧粉体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022408000002
    Figure 2025022408000002
  • Figure 2025022408000003
    Figure 2025022408000003
  • Figure 2025022408000001
    Figure 2025022408000001
Patent Text Reader

Abstract

To provide a method for producing a lithium metal composite oxide capable of producing with high production efficiency of a lithium metal composite oxide with few fine particles and high crystallinity, and a pressed powder body usable for the production method.SOLUTION: A method for producing a lithium metal composite oxide comprises a step of applying pressure P [MPa] to a powder containing a reaction product of a lithium compound and a metal composite compound to obtain a pressed powder body and a step of calcining the pressed powder body to obtain a lithium metal composite oxide. The ratio of the amount of Li to the total amount of metal elements other than Li contained in the powder is 1.00 or more and less than 1.14. The ratio S / P between the pressure P and the particle strength S [MPa] of the powder is 1.0 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a lithium metal composite oxide and a compact thereof. [Background technology]

[0002] Lithium metal composite oxides are used as positive electrode active materials for lithium secondary batteries. In order to improve the performance of the positive electrode active materials for lithium secondary batteries, attempts have been made to control the manufacturing methods of lithium metal composite oxides from various aspects.

[0003] The lithium metal composite oxide can be obtained by mixing a metal composite compound with a lithium compound and then baking the mixture.

[0004] For example, Patent Document 1 discloses a method of obtaining a positive electrode active material by forming a mixture of a nickel composite oxide and a lithium compound and firing the formed body. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP-A-2019-175694 Summary of the Invention [Problem to be solved by the invention]

[0006] As the production volume of positive electrode active materials increases, there is a demand for producing lithium metal composite oxides with few fine particles and high crystallinity with high production efficiency.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a method for producing a lithium metal composite oxide, which can produce a lithium metal composite oxide with few fine particles and high crystallinity with high production efficiency, and a powder compact that can be used in this production method. [Means for solving the problem]

[0008] The present invention includes the following aspects. [1] A step of applying a pressure P [MPa] to a powder containing a reaction product of a lithium compound and a metal composite compound to obtain a green compact; and sintering the powder compact to obtain a lithium metal composite oxide. The substance ratio of Li to the total amount of metal elements other than Li contained in the powder is 1.00 or more and less than 1.14, A method for producing a lithium metal composite oxide, wherein a ratio S / P of the pressure P to the particle strength S [MPa] of the powder is 1.0 or more. [2] The density of the green compact is 2.0 g / cm 3 More than 3.0g / cm 3 The method for producing a lithium metal composite oxide according to [1], wherein the [3] The method for producing a lithium metal composite oxide according to [1] or [2], wherein the reactant has a layered rock salt structure. [4] The method for producing a lithium metal composite oxide according to any one of [1] to [3], wherein in an X-ray diffraction measurement using CuKα radiation of the compressed powder body, the half-value width of a peak within a range of 2θ=18.7±2° is 0.50° or less. [5] The particle strength S is 50 MPa or more, The method for producing a lithium metal composite oxide according to any one of [1] to [4], wherein the S / P is 1.4 or more. [6] The LiOH and Li in the powder obtained by neutralization titration of the powder. 2 CO 3 The method for producing a lithium metal composite oxide according to any one of [1] to [5], wherein the proportions of are 0.60 mass % or more and 0.20 mass % or more, respectively, relative to the total mass of the powder. [7] The method for producing a lithium metal composite oxide according to any one of [1] to [6], wherein the pressure P is 10 MPa or more and less than 100 MPa. [8] The method for producing a lithium metal composite oxide according to any one of [1] to [7], wherein in the step of obtaining the lithium metal composite oxide, the compressed powder is fired at 700° C. or higher and 1,000° C. or lower in an atmosphere having an oxygen ratio of 50% or higher. [9] The method for producing a lithium metal composite oxide according to any one of [1] to [8], wherein the powder satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-xy):x:y...(1) (In formula (1), 0≦a<0.14, 0≦x≦0.5, 0≦y≦0.5, and 0≦x+y<1; M1 is at least one element selected from the group consisting of Co, Mn, and Al; and M2 is at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.)

[10] The method for producing a lithium metal composite oxide according to any one of [1] to [9], further comprising, before the step of obtaining the powder compact, a step of mixing the lithium compound and the metal composite compound and firing the mixture to obtain the powder.

[11] The method for producing a lithium metal composite oxide according to

[10] , wherein in the step of obtaining the powder, the lithium compound and the metal composite compound are fired at 300° C. or higher and 700° C. or lower in an atmosphere having an oxygen ratio of 50% or higher.

[12] The method for producing a lithium metal composite oxide according to any one of [1] to

[11] , wherein the powder compact is a molded body that is self-supporting without any external force other than gravity.

[13] A compact containing a reaction product of a lithium compound and a metal complex compound, The ratio of the amount of Li to the total amount of metal elements other than Li contained in the green compact is 1.00 or more and less than 1.14, The density of the green compact is 2.0 g / cm 3 More than 3.0g / cm 3 is less than A powder compact, in which, in an X-ray diffraction measurement of the powder compact using CuKα rays, the half-value width of a peak within a range of 2θ=18.7±2° is 0.50° or less.

[14] In the X-ray diffraction measurement, the crystallite size L of the peak present within the range of 2θ=18.7±2° 003 and the crystallite size L of the peak present in the range of 2θ = 44.6 ± 2° 104 Compared to L 003 / L 104The powder compact according to

[13] , wherein the powder compact has a refractive index of 1.2 or less.

[15] The powder compact according to

[13] or

[14] , wherein the powder compact satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-xy):x:y...(1) (In formula (1), 0≦a<0.14, 0≦x≦0.5, 0≦y≦0.5, and 0≦x+y<1; M1 is at least one selected from the group consisting of Co, Mn, and Al; and M2 is at least one selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.) Effect of the Invention

[0009] According to the present invention, it is possible to provide a method for producing a lithium metal composite oxide with high production efficiency, which can produce a lithium metal composite oxide with few fine particles and high crystallinity, and a green compact that can be used in this production method. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Diagram 2] FIG. 1 is a schematic diagram illustrating an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, a method for producing a lithium metal composite oxide and a compact according to one aspect of the present invention will be described. Preferred examples and conditions may be shared among the following embodiments. In the present specification, each term is defined as follows.

[0012] In this specification, metal composite compound powder is hereinafter referred to as "MCC", lithium metal composite oxide is hereinafter referred to as "LiMO", and cathode active material for lithium secondary batteries is hereinafter referred to as "CAM".

[0013] "Ni" refers to nickel atoms, not nickel metal. Similarly, "Co" and "Al" refer to cobalt atoms and aluminum atoms, etc., respectively.

[0014] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.

[0015] The "composition analysis" is performed by the following method. For example, the measurement object is dissolved in hydrochloric acid and then measured using an ICP optical emission spectrometer. As the ICP optical emission spectrometer, for example, Optima 7300 manufactured by PerkinElmer Co., Ltd. can be used. When analyzing a powder compact, the powder compact is crushed in a mortar until it becomes powdery, and the crushed product obtained is used as the measurement object.

[0016] LiMO and the reactant are particulate, are aggregates of particles, and contain at least one of primary particles and secondary particles. In this specification, the term "primary particles" refers to particles in which no clear grain boundaries are observed on the particle surface when the particles are observed at a magnification of 5000-20000 times using a scanning electron microscope or the like. The term "secondary particles" refers to particles in which a plurality of the primary particles are three-dimensionally bonded with gaps. That is, the secondary particles are aggregates of primary particles. The secondary particles have a spherical or nearly spherical shape. Usually, the secondary particles are formed by aggregating 10 or more primary particles. In addition, LiMO and the reactant may be composed of only primary particles, but it is desirable to include secondary particles from the viewpoint of improving the charge / discharge capacity of the battery and reducing the resistance.

[0017] The "particle strength S of the powder" (unit: MPa) can be measured and calculated as follows. Using a micro-compression tester (e.g., Shimadzu Corporation, MCT-510), 20 independent particles contained in the powder are randomly selected, and the particle diameter d (unit: mm) and crushing test force P (unit: N) are measured for each of the selected secondary particles, and the particle strength Cs is calculated using the following formula (X). P is the minimum test force at which the compressive displacement increases while the test force remains constant (at which point it is determined that the particle has been crushed) when the test force and the compressive displacement are gradually increased after the indenter comes into contact with the particle. d is the average value calculated by measuring the diameters in the X and Y directions in the microscopic observation image of the micro-compression tester. Cs=2.8P / πd 2 (X) The average value of Cs obtained for the 20 particles is the particle strength S of the powder.

[0018] "X-ray diffraction measurement" is performed as follows. An XRD pattern of the measurement object is obtained using an X-ray diffractometer (e.g., Ultima IV, manufactured by Rigaku Corporation) with CuKα as the radiation source and a measurement range of the diffraction angle 2θ of 10-90°. The obtained XRD pattern is analyzed using analysis software (e.g., integrated powder X-ray analysis software PDXL2, manufactured by Rigaku Corporation). When analyzing a powder compact, the powder compact is crushed in a mortar until it becomes powdery, and the crushed product obtained is used as the measurement object.

[0019] "LiOH and Li 2 CO 3 The "ratio of LiOH and LiOH to the total mass of the powder" can be calculated by the following neutralization titration method. 5 g of powder and 100 g of pure water are mixed to obtain a slurry. 0.1 mol / L hydrochloric acid is added dropwise to the filtrate obtained by filtering the slurry until the pH reaches 4.5. The titration amounts of 0.1 mol / L hydrochloric acid required to reach a pH of 8.3 and 4.5 (measurement temperature: 25°C) are S ml and T ml, respectively. Assuming that the lithium compounds that react with hydrochloric acid are lithium hydroxide and lithium carbonate, the ratio of LiOH and LiOH to the total mass of the powder is calculated by the following formula. 2 CO 3The ratio of LiOH and Li is calculated in the following formula. 2 CO 3 The molecular weight of is calculated assuming that the atomic weights of H are 1.000, Li are 6.941, C are 12.000, and O are 16.000. As an apparatus for dropping, for example, an automatic potentiometric titrator AT-610 manufactured by Kyoto Electronics Manufacturing Co., Ltd. can be used. Ratio of LiOH (mass%) = {0.1 × (TS) / 1000} × {73.882 / (20 × 60 / 100)} × 100 Li 2 CO 3 Ratio (mass%) = {0.1 × (2S-T) / 1000{ × {23.941 / (20 × 60 / 100)} × 100

[0020] In this specification, the "method of producing a positive electrode for a lithium secondary battery" is as follows. CAM, a conductive material (acetylene black), and a binder (PVdF) are added and kneaded so that the composition is CAM:conductive material:binder = 92:5:3 (mass ratio), to prepare a paste-like positive electrode mixture. When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.

[0021] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.

[0022] In this specification, the "method of producing a lithium secondary battery" is as follows. The following operations are carried out in a glove box with an argon atmosphere. The positive electrode for a lithium secondary battery produced by the "method of producing a positive electrode for a lithium secondary battery" is placed with the aluminum foil side facing down on the bottom cover of a part for a coin battery R2032 (manufactured by Hosen Co., Ltd.), and a laminated film separator (a 16 μm-thick laminate of a heat-resistant porous layer laminated on a polyethylene porous film) is placed on top of that. 300 μl of electrolyte is poured into this. The electrolyte is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a ratio of 30:35:35 (volume ratio), to which LiPF6 Use a solution prepared by dissolving to a concentration of 1 mol / l.

[0023] Next, using metallic lithium (with an area of 1.65 cm 2 or more) as the negative electrode, place the negative electrode on the upper side of the laminated film separator, cover it with an upper lid via a gasket, and crimp it with a crimper to fabricate a lithium secondary battery (coin-type half cell R2032).

[0024] The "initial discharge capacity" [mAh / g] means the value measured by performing charge and discharge of a lithium secondary battery fabricated by the "method for fabricating a lithium secondary battery" under the following conditions at an ambient temperature of 25°C.

[0025] (Charge and discharge test) Test temperature: 25°C Initial charge: Constant current and constant voltage charge, charge current 0.2 CA, cut-off voltage 4.3 V, cut-off current 0.05 CA Initial discharge: Constant current discharge, discharge current 0.2 CA, cut-off voltage 2.5 V

[0026] (Manufacture of LiMO) The method for manufacturing LiMO in one aspect of the present invention includes a step of applying a pressure P [MPa] to a powder containing a reaction product of a lithium compound and MCC to obtain a compacted powder, and a step of firing the compacted powder to obtain LiMO, wherein the molar ratio of Li to the total amount of metal elements other than Li contained in the powder is 1.00 or more and less than 1.14, and the ratio S / P of the pressure P to the particle strength S [MPa] of the powder is 1.0 or more.

[0027] The powder containing the reaction product of the lithium compound and MCC is a fired product obtained by mixing and firing the lithium compound and MCC.

[0028] (Compacted powder) First, the method of applying pressure P [MPa] to the powder to obtain a green compact includes filling the powder into a die, which is a mold for powder molding, and applying pressure by pressing a punch through the opening of the die. By filling the green compact into the sintering container, the amount of reactants loaded per container increases, improving the sintering process efficiency and improving the production efficiency of LiMO. In addition, forming a green compact improves the contact between the reactants, improving the thermal diffusion characteristics during sintering of the green compact.

[0029] The ratio S / P of the pressure P [MPa] applied to the powder to the particle strength S [MPa] of the powder is 1.0 or more, and preferably 1.4 or more. When a pressure greater than the particle strength S of the powder is applied (i.e., when S / P is less than 1.0), the particles in the powder are likely to be destroyed. When the particles are destroyed, fine particles are likely to be generated, and the resulting LiMO is likely to contain fine particles. When LiMO containing fine particles is used as CAM, the mass that does not contact the conductive assistant and does not contribute to charging and discharging increases, and the charging and discharging capacity is likely to decrease. In addition, when S / P is less than 1.0, cracks are generated inside the particles, lithium ion diffusion in the particles is hindered, and resistance deterioration during charging and discharging is likely to occur. In order to mold the powder with an appropriate pressure, S / P is preferably 10.0 or less, more preferably 6.0 or less.

[0030] The upper and lower limits of S / P can be combined in any combination. In order to suppress the generation of fine particles, S / P is preferably 1.0 to 10.0, and more preferably 1.4 to 6.0.

[0031] The pressure P is preferably 10 MPa or more, more preferably 20 MPa or more. The pressure P is preferably less than 200 MPa, more preferably 100 MPa or less, and even more preferably 50 MPa or less. The pressure P is preferably 10 MPa or more and less than 200 MPa, more preferably 20 to 100 MPa, and even more preferably 20 to 50 MPa. When the pressure P is equal to or more than the lower limit, the powder can be molded with an appropriate strength, the density of the green compact can be set in the range described below, and the production efficiency of LiMO can be improved. When the pressure P is equal to or less than the upper limit, the resulting LiMO is less likely to contain fine particles.

[0032] The particle strength S is preferably 50 MPa or more. The particle strength S is preferably 300 MPa or less, more preferably 250 MPa or less, and even more preferably 200 MPa or less. The particle strength S is preferably 50 to 300 MPa, more preferably 50 to 250 MPa, and even more preferably 50 to 200 MPa. When the particle strength S is equal to or greater than the lower limit, it can be said that the MCC and the lithium compound react appropriately, and crystal growth can be promoted during sintering of the green compact. In addition, since the range of pressure that can be applied to the powder is expanded, the density of the obtained green compact can be increased, and the production efficiency of LiMO can be improved. When the particle strength S is equal to or less than the upper limit, the heat load during synthesis of the reactant from the MCC and the lithium compound can be reduced, and the scale of the sintering furnace can be reduced.

[0033] The density of the green compact is 2.0 g / cm 3 It is preferable that the content is 2.3 g / cm or more. 3 It is more preferable that the density of the green compact is 3.0 g / cm 3 Preferably less than 2.9 g / cm 3 It is more preferable that the density of the green compact is 2.0 g / cm or less. 3 More than 3.0g / cm 3 Preferably less than 2.3-2.9 g / cm 3 When the density of the green compact is equal to or higher than the lower limit, the amount of reactants packed into a firing vessel can be increased when synthesizing LiMO from the green compact, and the amount of synthesis per unit volume increases, improving the production efficiency of LiMO. 3 When the content is less than 100%, adhesion between particles after the compact is heat-treated can be suppressed, and fine particles are less likely to be generated and less likely to be included in the LiMO.

[0034] When the green compact is cylindrical, the "density of the green compact" is calculated as follows: First, the weight m [g] of the green compact is measured using a weighing scale. Next, while the green compact is standing on its own, its height h [mm] is measured using a height gauge. The diameter d [mm] of the cylinder is determined by measuring the diameter in three directions, each 60° apart, at positions ±0.5 mm in the height direction using a vernier caliper, and taking the average value. The density ρ of the green compact is calculated using the weight m, height h of the green compact, and diameter d as follows: ρ=m / (h×d 2 / 4).

[0035] If the green compact is a rectangular prism, the weight m [g] of the green compact is measured with a weighing scale, and the long side b, short side c, and height h of the green compact are measured with a vernier caliper. The density ρ of the green compact is then calculated by "ρ = m / (b x c x h)". If the green compact is neither cylindrical nor rectangular prism, the weight m [g] of the green compact is measured with a weighing scale, and the volume V is measured using a non-contact three-dimensional measuring device or similar. The density ρ of the green compact is then calculated by "ρ = m / V".

[0036] Conventionally, a mixture of a lithium compound and MCC is sintered in a sintering furnace or the like while being housed in a container such as a case. However, when the mixture is sintered in a container, the thermal diffusivity of the mixture in the container is low, and a temperature difference occurs in the container, so it is not easy to obtain LiMO with high crystallinity. In addition, the density of the green compact obtained by molding the mixture does not change significantly compared to when it is not molded, so the amount of filling into the container does not change significantly, making it difficult to improve production efficiency. The above-mentioned LiMO production method uses a reactant of a lithium compound and MCC, so the density of the obtained green compact is high, the amount of filling into the container can be increased, and the production efficiency of LiMO with few fine particles and high crystallinity can be improved.

[0037] The equipment used to obtain the green compact includes a press, for example, a uniaxial press or a tablet press. The obtained green compact is preferably a molded body that stands on its own without any external force other than gravity. In other words, it is preferable that the green compact can maintain its shape even when placed on a mounting plate or the like, not in a container or the like. Therefore, the green compact can be fired while placed on a mounting plate or the like. In this case, the surfaces of the green compact other than the bottom surface are exposed to the firing atmosphere, which promotes heat transfer and radiative heat transfer from the firing atmosphere, improves thermal diffusion to the inside of the green compact, and allows firing to be performed uniformly. As a result, LiMO with high crystallinity can be produced. In addition, if a container or the like shaped to accommodate the powder becomes a mounting plate, the weight and volume of the container itself will be reduced, so that more reactants can be charged into the firing furnace per unit time, thereby improving the production efficiency of LiMO.

[0038] The shape of the powder compact is not particularly limited, but examples thereof include a square prism and a cylinder, taking into consideration the fact that the powder compact is produced by applying pressure. The shape of the powder compact is preferably a flat shape, so that the powder compact can be uniformly fired. For example, when the powder compact is a cylinder or a square prism, it is preferable that the area of ​​the bottom and top faces is large and the area of ​​the side faces is small.

[0039] In the X-ray diffraction measurement of the powder compact using CuKα radiation, the half-width A of the peak present within the range of 2θ=18.7±2° is preferably 0.50° or less. When the half-width A is 0.50° or less, it can be said that the crystals of the plane belonging to the peak present within the range of 2θ=18.7±2° have grown appropriately, and the powder compact contains a reaction product of the lithium compound and MCC. The half-width A of the powder compact produced using a mixture of the lithium compound and MCC is likely to exceed 0.50°. The upper limit of the half-width A is preferably 0.40° or less, more preferably 0.30° or less.

[0040] The half-width A is preferably 0.19° or more. When the half-width A is 0.19° or more, the crystallinity of the reactant is not too high, and an appropriate amount of residual lithium component is contained during firing, so that an inactive molten salt is formed during firing and crystal growth can be promoted. The fired product obtained by firing a lithium compound and MCC at a high temperature (for example, a temperature exceeding 700°C) may have too high a crystallinity, and the half-width A may be less than 0.19°. The half-width A is preferably 0.20° or more, more preferably 0.21° or more. The half-width A is preferably 0.19-0.50°, more preferably 0.20-0.40°, and even more preferably 0.21-0.30°. When the half-value width A is within the above range, LiMO having high crystallinity and few fine particles can be obtained.

[0041] In the X-ray diffraction measurement of the compact using CuKα radiation, the crystallite size L of the peak present within the range of 2θ=18.7±2° 003 and the crystallite size L of the peak present in the range of 2θ = 44.6 ± 2° 104 Compared to L 003 / L 104 is preferably 1.2 or less, and more preferably 1.1 or less. 003 / L 104 When is equal to or less than the upper limit, the crystal anisotropy of the reaction product of the lithium compound and MCC is limited, so that the anisotropy of the strength of the crystallite against external forces is also limited, and the particle strength S of the powder can be increased to an appropriate value. As a result, the generation of fine particles due to particle cracking during the production of the green compact can be suppressed, and the amount of fine particles contained in the obtained LiMO can be reduced.

[0042] Also L 003 / L 104 is preferably 0.90 or more, and more preferably 0.92 or more. 003 / L 104 When is equal to or larger than the lower limit, crystal growth in the layer direction during firing is easily promoted, and the crystallinity of the obtained LiMO can be increased. L 003 / L 104is preferably 0.90 to 1.2, and more preferably 0.92 to 1.1.

[0043] The powder compact preferably satisfies the formula (1) described below. Also, the powder compact is preferably represented by the formula (2) described below.

[0044] (Firing of powder compact) LiMO is obtained by sintering the compact. The sintering temperature is preferably 700 to 1000°C, more preferably 710 to 950°C, further preferably 720 to 900°C, and particularly preferably 730 to 850°C. When the sintering temperature is equal to or higher than the lower limit of the above range, LiMO having a strong crystal structure can be obtained. When the sintering temperature is equal to or lower than the upper limit of the above range, the volatilization of lithium ions on the surface of the LiMO particles can be suppressed. In addition, when the sintering temperature is equal to or lower than the upper limit of the above range, excessive adhesion between particles can be suppressed, and therefore the crushability can be improved.

[0045] In this specification, the firing temperature refers to the temperature of the atmosphere in the firing furnace, and means the maximum holding temperature (maximum holding temperature). When the process of firing the powder compact has multiple firing stages, the firing temperature refers to the temperature of the stage in which the firing is performed at the highest holding temperature among the firing stages.

[0046] The retention time during sintering the compact is preferably 1 to 10 hours, more preferably 2 to 8 hours. When the retention time during sintering the compact is equal to or less than the upper limit of the above range, the volatilization of lithium ions is suppressed, and the deterioration of battery performance is suppressed. When the retention time during sintering the compact is equal to or less than the upper limit of the above range, excessive adhesion between particles can be suppressed, and the crushability can be improved. When the retention time during sintering the compact is equal to or more than the lower limit of the above range, the inside of the compact is thermally diffused to an appropriate temperature, the development of crystals is promoted, and the initial discharge capacity can be improved.

[0047] The rate of temperature rise until the maximum holding temperature is reached is preferably 50° C. / hour or more, more preferably 100° C. / hour or more, and even more preferably 150° C. / hour or more. The rate of temperature rise until the maximum holding temperature is reached is calculated from the time from the start of temperature rise in the firing furnace until the holding temperature is reached.

[0048] The step of sintering the green compact preferably has multiple sintering stages with different sintering temperatures. For example, it may have a first sintering stage and a second sintering stage in which sintering is performed at a higher temperature than the first sintering stage. It may also have sintering stages with different sintering temperatures and sintering times.

[0049] The firing atmosphere may be air, oxygen, nitrogen, argon or a mixture of these gases depending on the desired composition, and is preferably an oxygen-containing atmosphere.

[0050] The oxygen ratio in the firing atmosphere is preferably 50% or more, and more preferably 70% or more. When the oxygen ratio in the firing atmosphere is 50% or more, firing is easily performed without variation throughout the compact. As a result, an increase in the ratio of rock salt structures in LiMO can be suppressed.

[0051] The firing furnace used for firing the compact and producing the reactant described below may be, for example, a continuous firing furnace, such as a tunnel furnace or a roller hearth kiln.

[0052] (powder containing reactants) The ratio of the amount of Li to the total amount of metal elements other than Li contained in the powder is preferably 1.03 or more, more preferably 1.05 or more. When the ratio of the amount of Li is equal to or more than the lower limit, the amount of LiOH and Li contained in the powder is reduced. 2 CO 3 The unreacted lithium compounds (hereinafter, sometimes referred to as residual lithium compounds) act as a binder, and can improve the moldability of the green compact.

[0053] The Li mass ratio is preferably 1.12 or less, more preferably 1.10 or less. In the present invention, a powder is subjected to pressure to produce a green compact having a high density, and the green compact obtained is fired. Therefore, if the green compact contains too much residual lithium compound, the residual lithium compound aggregates in the gaps between particles of the green compact and functions locally as an inactive molten salt, which may cause uneven particle growth. In addition, when the reactant in the powder contains secondary particles, the residual lithium compound that functions locally as an inactive molten salt may cause a difference in crystal growth between the primary particles constituting the secondary particles, and the generated internal stress may exceed the binding force between the primary particles, causing the primary particles to fall off from the secondary particles. In addition, the residual lithium compound aggregates inside the green compact, making it difficult to supply the oxidizing gas in the firing atmosphere, so that the reactant with a layered rock salt structure contained in the green compact may be locally reduced, and the proportion of crystals having a rock salt structure may increase among the crystals of LiMO obtained. Furthermore, the residual lithium compound may easily cause adhesion between particles, which may cause poor crushability. If the substance ratio of Li is equal to or less than the upper limit, the powder does not contain excessive residual lithium, so that the proportion of crystals having a rock salt structure in the obtained LiMO is reduced and the crushability can be improved. The substance ratio of Li is preferably 1.03 to 1.12, and more preferably 1.05 to 1.10.

[0054] The proportion of LiOH determined by neutralization titration of the powder is preferably 0.60% by mass or more, more preferably 1.00% by mass or more, based on the total mass of the powder. The proportion of LiOH is preferably 2.00% by mass or less, more preferably 1.70% by mass or less, based on the total mass of the powder.

[0055] Li determined by powder neutralization titration 2 CO 3 The proportion of Li is preferably 0.20% by mass or more, and more preferably 0.50% by mass or more, based on the total mass of the powder. 2 CO 3The proportion of is preferably 1.00 mass % or less, and more preferably 0.80 mass % or less, relative to the total mass of the powder.

[0056] LiOH and Li 2 CO 3 The upper and lower limits of the ratio can be arbitrarily combined. The ratio of LiOH is preferably 0.60-2.00 mass% and more preferably 1.00-1.70 mass% of the total mass of the powder. 2 CO 3 The proportion of is preferably 0.20-1.00 mass %, more preferably 0.50-0.80 mass %, relative to the total mass of the powder.

[0057] LiOH and Li 2 CO 3 When the ratios of LiOH and Li in the powder are equal to or higher than the above lower limits, 2 CO 3 LiOH and Li 2 CO 3 When the proportions are each equal to or less than the above upper limit, the crushability can be improved.

[0058] The powder preferably satisfies the following formula (1): The reactant is preferably represented by the following formula (2). Li:Ni:M1:M2=(1+a):(1-xy):x:y...(1) Li a [Li(Ni) (1-x-y) M1 x M2 y ) 1-a ]O 2 (2) (In the formulas (1) and (2), 0≦a<0.14, 0≦x≦0.5, 0≦y≦0.5, and 0≦x+y<1; M1 is at least one selected from the group consisting of Co, Mn, and Al; and M2 is at least one selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.)

[0059] From the viewpoint of improving the moldability of the green compact, a is preferably 0.03 or more, and more preferably 0.05 or more. When a is equal to or more than the lower limit, the pressure P required for producing the green compact can be reduced, and the scale of the press used for producing the green compact can be reduced. Note that formula (1) is a ratio including both the reactants and the residual lithium compounds contained in the powder.

[0060] From the viewpoint of reducing the proportion of crystals having a rock salt structure in the obtained LiMO and improving crushability, a is preferably 0.12 or less, and more preferably 0.10 or less.

[0061] The upper limit and lower limit of a can be arbitrarily combined. a is preferably from 0.03 to 0.12, and more preferably from 0.05 to 0.10.

[0062] From the viewpoint of obtaining a lithium secondary battery with high charge / discharge capacity, x+y is preferably 0.50 or less, and more preferably 0.20 or less, and preferably 0.05 or more, and more preferably 0.10 or more.

[0063] The upper limit and lower limit of x+y can be combined in any combination. x+y is preferably from 0.05 to 0.50, more preferably from 0.05 to 0.20, and even more preferably from 0.10 to 0.20.

[0064] From the viewpoint of obtaining a lithium secondary battery having high rate characteristics and cycle retention rate, x is preferably 0.005 or more, and more preferably 0.01 or more, and preferably 0.2 or less, and more preferably 0.15 or less.

[0065] The upper limit and lower limit of x can be combined in any desired manner. x is preferably from 0.005 to 0.2, and more preferably from 0.01 to 0.15.

[0066] When the powder contains M2, from the viewpoint of obtaining a lithium secondary battery having high rate characteristics and cycle retention rate, y is preferably 0.005 or more, more preferably 0.01 or more, and is preferably 0.20 or less, more preferably 0.10 or less.

[0067] The upper limit and lower limit of y can be arbitrarily combined. y is preferably 0 to 0.20, more preferably 0.005 to 0.20, and even more preferably 0.01 to 0.10.

[0068] From the viewpoint of obtaining a lithium secondary battery having high rate characteristics and cycle retention rate, M2 is preferably one or more elements selected from the group consisting of Ti, Mg, W, B, Nb, and Zr, and more preferably one or more elements selected from the group consisting of W, B, Nb, and Zr.

[0069] The reactant preferably has a layered rock salt structure, more preferably a hexagonal crystal structure or a monoclinic crystal structure. The crystal structure of the reactant can be confirmed by X-ray diffraction measurement using an X-ray diffraction device (e.g., Ultima IV, manufactured by Rigaku Corporation).

[0070] The hexagonal crystal structure is P3, P3 1 , P3 2 , R3, P-3, R-3, P312, P321, P3 1 12, P3 1 21, P3 2 12, P3 2 21, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P6 1 , P6 5 , P6 2 , P6 4 , P6 3 , P-6, P6 / m, P6 3 / m, P622, P6 1 22, P6 5 22, P6 2 22, P6 4 22, P63 22, P6mm, P6cc, P6 3 cm, P6 3 mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P6 3 / mcm and P6 3 / mmc.

[0071] In addition, the monoclinic crystal structure is P2, P2 1 , C2, Pm, Pc, Cm, Cc, P2 / m, P2 1 / m, C2 / m, P2 / c, P2 1 It is assigned to any one space group selected from the group consisting of C2 / c, C3 / c, and C4 / c.

[0072] Among these, in order to obtain a lithium secondary battery with a high initial discharge capacity, it is more preferable that the reactant has a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to the space group C2 / m.

[0073] <Lithium compounds and MCC> The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride. Of these, lithium hydroxide and lithium carbonate or a mixture thereof are preferred.

[0074] MCC may be any of metal composite hydroxides, metal composite oxides, and mixtures thereof. The metal composite hydroxides and metal composite oxides are preferably compounds containing M1 and M2 in the molar ratio represented by the following formula (A) and represented by the following formula (A'). Note that x, y, M1, and M2 in formulas (A) and (A') are the same as x, y, M1, and M2 in formula (1). Ni:M1:M2=(1-xy):x:y (A) Ni (1-x-y) M1 x M2 y O α (OH) 2-β (A') (It is preferable that formula (A') satisfies 0≦α≦3, −0.5≦β≦2, and β-α<2.)

[0075] MCC can be produced by a batch coprecipitation method or a continuous coprecipitation method. Specifically, by the continuous coprecipitation method described in JP-A-2002-201028, a nickel salt solution, a metal salt solution of element M1, and, if necessary, a metal salt solution of element M2 and a complexing agent are reacted to produce the metal composite hydroxide represented by the formula (A'). For example, when producing a metal composite hydroxide containing Ni, Co, and Mn, a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent are reacted to produce Ni (1-x-y) Co e Mn f (OH) 2 A metal composite hydroxide represented by (e+f=x) is produced. This metal composite hydroxide may be used as MCC, or a metal composite oxide obtained by heating the metal composite hydroxide may be used as MCC.

[0076] (Powder manufacturing) The method for producing LiMO may include a step of mixing a lithium compound and MCC and sintering the mixture to obtain a powder before the step of obtaining a compact. The lithium compound and MCC are preferably mixed in a ratio that satisfies the above formula (1).

[0077] The firing temperature is preferably 300 to 700°C, more preferably 400 to 680°C, and even more preferably 450 to 650°C. When the firing temperature is equal to or higher than the lower limit of the above range, the resulting powder does not contain an excessive amount of unreacted lithium compound, and the density of the green compact can be increased. When the firing temperature is equal to or lower than the upper limit of the above range, the anisotropy of the crystal growth of the reactant can be restricted, that is, the anisotropy of the strength of the crystallite against external forces can be restricted, and the particle strength S of the powder can be increased to an appropriate value. As a result, the generation of fine particles due to particle cracking during the production of the green compact can be suppressed, and the fine particles contained in the resulting LiMO can be reduced. In addition, by adjusting the firing temperature to the above range, the half-width A and L of the green compact can be reduced. 003 / L104 can be adjusted to the above range.

[0078] The retention time during firing is preferably 1 to 10 hours, more preferably 2 to 7 hours. When the retention time during firing is equal to or less than the upper limit of the above range, the anisotropy of the crystal growth of the reactant can be restricted, that is, the anisotropy of the strength of the crystallite against external forces can be restricted, and the particle strength S can be increased to an appropriate value. As a result, the generation of fine particles due to particle cracking during the production of the powder compact can be suppressed, and the fine particles contained in the obtained LiMO can be reduced. When the retention time during firing is equal to or more than the lower limit of the above range, a powder having uniform crystallinity can be produced.

[0079] As the firing atmosphere, air, oxygen, nitrogen, argon or a mixture of these gases is used depending on the desired composition, and multiple firing steps are carried out if necessary. The firing atmosphere is preferably an oxygen-containing atmosphere.

[0080] The oxygen ratio in the firing atmosphere is preferably 50% or more, more preferably 70% or more. When the oxygen ratio in the firing atmosphere is 50% or more, the reaction between the lithium compound and MCC is promoted, and a powder that contributes to improving the crystallinity of LiMO can be produced.

[0081] The MCC and the lithium compound may be sintered in the presence of an inert flux. The inert flux may be added to such an extent that the initial capacity of the resulting battery using LiMO as CAM is not impaired, and may remain in the powder. As the inert flux, for example, the inert flux described in WO2019 / 177032A1 may be used.

[0082] <limo> The above LiMO is preferably represented by the following formula (I). Li a [Li(Ni (1-x-y) M1 x M2 y ) 1-a O 2 ···(I)

[0083] In addition, a, x, y, M1, and M2 in formula (I) are the same as a, x, y, M1, and M2 in formula (1).

[0084] <Pressed powder As another aspect of the present invention, the pressed powder contains a reaction product of a lithium compound and a metal composite compound, the molar ratio of Li to the total amount of metal elements other than Li contained in the pressed powder is 1.00 or more and less than 1.14, and the density of the pressed powder is 2.0 g / cm 3 or more and less than 3.0 g / cm 3 In the X-ray diffraction measurement using the CuKα ray of the pressed powder, the half-value width of the peak existing within the range of 2θ = 18.7 ± 2° is 0.50° or less.

[0085] The pressed powder of this aspect may have the characteristics of the pressed powder described in <Manufacture of LiMO>, and the descriptions of <Manufacture of LiMO> can be arbitrarily combined.

[0086] The above pressed powder has excellent formability, and LiMO obtained by firing the above pressed powder also has excellent crushability. Therefore, the production efficiency of LiMO can be increased. In addition, LiMO obtained by using the above pressed powder has few fine particles, high crystallinity, a small proportion of rock salt structure, and is also less likely to have a decrease in the initial discharge capacity.

[0087] The "moldability of the green compact" is evaluated as follows: A die is filled with powder, a punch is inserted and uniaxial pressing is performed, and then the pressure is released and the die is slid to remove the green compact inside. If the green compact stands on its own and can be picked up with tweezers, it is rated as A; if it stands on its own but crumbles when picked up with tweezers, it is rated as B; and if it does not stand on its own immediately after being removed (i.e. does not maintain its shape), it is rated as C. When it is rated as A, it is evaluated as having the highest compact moldability and the highest LiMO production efficiency, and when it is rated as C, it is evaluated as having the lowest compact moldability and LiMO production efficiency.

[0088] "Crushability" is evaluated as follows: when LiMO is placed in a mortar, a pestle is placed on the mortar, and the LiMO is crushed by lightly pressing the pestle into the mortar, it is rated as A; when LiMO is crushed by lightly tapping with the pestle, it is rated as B; and when LiMO cannot be crushed by tapping with the pestle alone, but is crushed by tapping the back of the mortar with a plastic hammer while the pestle is in contact with the LiMO, it is rated as C. When it is rated as A, it is rated as the highest crushability and the highest LiMO production efficiency, and when it is rated as C, it is rated as the lowest crushability and the lowest LiMO production efficiency.

[0089] The presence or absence of fine particles in LiMO is judged as follows: The particle size distribution of the powder containing the reaction product of lithium compound and MCC is measured using a laser diffraction particle size distribution analyzer, and the smallest particle size detected is called D MIN-0 Next, the particle size distribution of LiMO was measured in the same manner, and the smallest particle size detected was designated as D MIN Let us assume that. D MIN <D MIN-0 If the above condition is met, it is judged that fine particles are present, and D MIN ≧D MIN-0 When the result is positive, it is determined that there are no fine particles. As the laser diffraction particle size distribution analyzer, for example, MT3000II manufactured by Microtrack Bell can be used.

[0090] The "crystallinity of LiMO" is evaluated as follows. Using LiMO as the measurement object, the L of LiMO is measured by the method described in the "X-ray diffraction measurement" above. 003 In this embodiment, L 003 When the thickness is 70 nm or more, the crystallinity is evaluated as high.

[0091] The "proportion of rock salt structure" relative to the total crystals contained in LiMO is measured as follows. LiMO is used as the measurement object, and an XRD pattern is obtained by measuring using the method described in the "X-ray diffraction measurement" above. A Rietveld analysis is performed on the XRD pattern, and the proportion of the rock salt structure is calculated by fitting using the least squares method with a model of the coexistence of the layered rock salt crystal structure and the rock salt structure. If the proportion of the rock salt structure is 0.8% by volume or less, the proportion of the rock salt structure is evaluated to be low.

[0092] <cam> The CAM of the present embodiment includes the above-mentioned LiMO. The CAM may be composed of LiMO. When such a CAM is used, a lithium secondary battery having an improved initial discharge capacity is easily obtained.

[0093] <Lithium secondary battery> The configuration of a lithium secondary battery suitable for use with the CAM will be described below, along with a positive electrode for a lithium secondary battery (hereinafter, sometimes referred to as a positive electrode) suitable for use with the CAM.

[0094] An example of a suitable lithium secondary battery for use with the CAM includes a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.

[0095] An example of a lithium secondary battery has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode.

[0096] 1 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.

[0097] First, as shown in the partially enlarged view of FIG. 1 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.

[0098] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.

[0099] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of the negative electrode active material alone. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.

[0100] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.

[0101] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut in a direction perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.

[0102] The shape of a lithium secondary battery having such an electrode group 4 may be any shape specified by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes may be used.

[0103] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.

[0104] The positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery can be, for example, the configurations, materials, and manufacturing methods described in

[0113] to

[0140] of WO2022 / 113904A1.

[0105] <All-solid-state lithium secondary battery> Next, a positive electrode using the CAM according to one embodiment of the present invention and an all-solid-state lithium secondary battery including this positive electrode will be described while explaining the configuration of the all-solid-state lithium secondary battery.

[0106] FIG. 2 is a schematic diagram showing an example of the all-solid-state lithium secondary battery of this embodiment. The all-solid-state lithium secondary battery 1000 shown in FIG. 2 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a positive electrode active material and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400. The materials constituting each member will be described later.

[0107] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.

[0108] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.

[0109] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.

[0110] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .

[0111] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.

[0112] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).

[0113] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.

[0114] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in

[0151] to

[0181] of WO2022 / 113904A1 can be used.

[0115] The positive electrode having the above-mentioned configuration has the above-mentioned CAM, and therefore can provide a lithium secondary battery with a large initial discharge capacity.

[0116] Furthermore, the lithium secondary battery having the above-mentioned configuration has a large initial discharge capacity because it has the above-mentioned positive electrode.

[0117] In another aspect, the present invention includes the following embodiments.

[16] A step of applying a pressure P [MPa] to a powder containing a reaction product of a lithium compound and a metal composite compound to obtain a green compact; and sintering the powder compact to obtain LiMO. The ratio of the amount of Li to the total amount of metal elements other than Li contained in the powder is 1.00 to 1.10; A method for producing LiMO, wherein the ratio S / P of the pressure P to the particle strength S [MPa] of the powder is 1.4-6.0.

[17] The density of the green compact is 2.3-2.9 g / cm 3 The method for producing LiMO described in

[16] ,

[18] The method for producing LiMO according to

[16] or

[17] , wherein the reactant has a layered rock salt structure.

[19] The method for producing LiMO according to any one of

[16] to

[18] , wherein the half-value width A is 0.21-0.30°.

[20] The method for producing LiMO according to any one of

[16] to

[19] , wherein the particle strength S is 50 to 200 MPa.

[21] The LiOH and Li in the powder obtained by neutralization titration of the powder. 2 CO 3 The method for producing LiMO according to any one of

[16] to

[20] , wherein the proportions of are 1.00-1.70 mass% and 0.50-0.80 mass%, respectively, relative to the total mass of the powder.

[22] The method for producing LiMO according to any one of

[16] to

[21] , wherein the pressure P is 20 to 50 MPa.

[23] The method for producing LiMO according to any one of

[16] to

[22] , wherein in the step of obtaining LiMO, the green compact is fired at 730-850°C in an atmosphere having an oxygen ratio of 70% or more.

[24] The method for producing LiMO according to any one of

[16] to

[23] , wherein the powder satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-xy):x:y...(1) (In formula (1), 0.05≦a≦0.10, 0.01≦x≦0.15, 0≦y≦0.20, and 0.05≦x+y≦0.20; M1 is at least one element selected from the group consisting of Co, Mn, and Al; and M2 is at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.)

[25] The method for producing LiMO according to any one of

[16] to

[24] , further comprising the step of mixing the lithium compound and the metal composite compound and firing the mixture to obtain the powder, prior to the step of obtaining the powder compact.

[26] The method for producing LiMO according to

[25] , wherein in the step of obtaining the powder, the lithium compound and the metal composite compound are sintered at 450-650°C in an atmosphere having an oxygen ratio of 70% or more.

[27] The method for producing LiMO according to any one of

[16] to

[26] , wherein the powder compact is a molded body that is self-supporting without any external force other than gravity.

[28] A compact containing a reaction product of a lithium compound and a metal complex compound, The ratio of the amount of Li to the total amount of metal elements other than Li contained in the green compact is 1.00-1.10; The density of the green compact is 2.3-2.9g / cm 3 and The half width A is 0.30° or less.

[29] Said L 003 / L 104

[28] . The powder compact according to

[28] , wherein

[30] The powder compact according to

[28] or

[29] , wherein the powder compact satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-xy):x:y...(1) (In formula (1), 0.05≦a≦0.10, 0.01≦x≦0.15, 0≦y≦0.20, and 0.05≦x+y≦0.20; M1 is at least one selected from the group consisting of Co, Mn, and Al; and M2 is at least one selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.) EXAMPLES

[0118] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.

[0119] <Composition analysis> The compositional analysis of the powder or the compacted powder produced by the method described below (the composition ratio of each element and the molar ratio of Li to the total amount of metal elements other than Li [Li / (M1+M2)]) was carried out by the method described in the above-mentioned "Compositional Analysis".

[0120] <Particle strength S of the powder> The particle strength S of the powder produced by the method described below was measured by the method described in the above-mentioned "Particle strength S of the powder".

[0121] <X-ray diffraction measurement> The full width at half maximum A of the mixture and the compacted powder, and the L of the compacted powder produced by the method described below 003 / L 104 were measured by the method described in the above-mentioned "X-ray diffraction measurement". The L of LiMO 003 was measured by the method described in the above-mentioned "Crystallinity of LiMO".

[0122] <Density of the compacted powder> The density of the compacted powder produced by the method described below was measured by the method described in the above-mentioned "Density of the compacted powder".

[0123] <LiOH and Li 2 CO 3 Ratio The ratio of LiOH and Li contained in the powder produced by the method described below 2 CO 3 was measured by the method described in the above-mentioned "Ratio of LiOH and Li 2 CO 3 Ratio".

[0124] <Formability of the compacted powder> The formability of the compacted powder produced by the method described below was evaluated by the method described in the above-mentioned "Formability of the compacted powder".

[0125] <Crushability> The crushability of LiMO produced by the method described below was evaluated by the method described in the above-mentioned "Crushability".

[0126] <Ratio of the rock salt structure> The ratio of the rock salt structure to the entire LiMO crystal was measured by the method described in the above-mentioned "Ratio of Rock Salt Structure".

[0127] <Presence or Absence of Fine Particles Contained in LiMO> The presence or absence of fine particles contained in LiMO was evaluated by the method described in the above-mentioned "Presence or Absence of Fine Particles Contained in LiMO".

[0128] <Initial Discharge Capacity> Regarding the lithium secondary battery fabricated as described in the above-mentioned "Method for Fabricating a Positive Electrode for a Lithium Secondary Battery" and "Method for Fabricating a Lithium Secondary Battery", the initial discharge capacity was measured by the method described in the above-mentioned "Initial Discharge Capacity".

[0129] (Example 1) After adding water into a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 50 °C.

[0130] An aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution were mixed so that the molar ratio of Ni, Co, and Mn was 0.85:0.05:0.10 to prepare a mixed solution.

[0131] Next, an aqueous ammonium sulfate solution was continuously added as a complexing agent to this mixed solution in the reaction tank under stirring. An aqueous sodium hydroxide solution was dropped in a timely manner so that the pH of the mixed solution in the reaction tank became 12.1 (measurement temperature: 40 °C) to obtain Reaction Precipitate 1.

[0132] After washing Reaction Precipitate 1 with pure water, it was dehydrated with a centrifuge. The dehydrated Reaction Precipitate 1 was dried at 105 °C for 20 hours to obtain MCC-1, which is a metal composite hydroxide.

[0133] Lithium hydroxide was weighed so that the amount (molar ratio) of Li to the total amount 1 of Ni, Co, and Mn contained in MCC-1 was 1.05. MCC-1 and lithium hydroxide were mixed to obtain Mixture 1.

[0134] Mixture 1 was kept in a sintering furnace under a 100% oxygen atmosphere at 650°C for 5 hours to obtain Powder 1 containing the reactants. Composition analysis of Powder 1 showed that in formula (1), a=0.05, x=0.15, and y=0, and element M1 was Mn and Co. Furthermore, X-ray diffraction measurement showed that Powder 1 had a layered rock salt structure.

[0135] Powder 1 was filled into a powder molding die (LaboNect Lab Die, specifications: φ15 mm × L30 mm), and a uniaxial press (Riken Kikai Co., Ltd., product numbers CD-10-10 (stand) · D1-300 (hydraulic cylinder)) was used to apply a pressure of 50 MPa to the die at room temperature to obtain a cylindrical green compact 1 with a diameter of 15 mm and a height of 13 mm. Green compact 1 was self-supporting.

[0136] The powder compact 1 was placed in a sintering furnace, and the temperature inside the furnace was raised to 800°C at a heating rate of 300°C / h under a 100% oxygen atmosphere. When 800°C was reached, heating was stopped and the furnace was left to stand until the temperature inside the furnace dropped to 50°C or below, yielding LiMO-1.

[0137] Example 2 Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount of Ni, Co, and Mn contained in MCC-1, which was 1, was 1.10. Mixture 2 was obtained by mixing MCC-1 and lithium hydroxide.

[0138] Mixture 2 was kept in a sintering furnace under a 100% oxygen atmosphere at 650°C for 5 hours to obtain powder 2 containing a reactant. Compact 2 and LiMO-2 were obtained in the same manner as in Example 1, except that powder 2 was used. Composition analysis of powder 2 revealed that in formula (1), a=0.10, x=0.15, and y=0, and element M1 was Mn and Co. Furthermore, X-ray diffraction measurement revealed that powder 2 had a layered rock salt structure. Compact 2 was self-supporting.

[0139] Example 3 LiMO-3 was obtained in the same manner as in Example 1, except that the powder 1 was filled into a powder molding die (LaboDie manufactured by LabNect, specifications: φ30 mm × L30 mm), and a pressure of 20 MPa was applied to the die using the above-mentioned uniaxial press to obtain a cylindrical powder compact 3 having a diameter of 30 mm and a height of 3 mm. The powder compact 3 was self-supporting.

[0140] Example 4 The powder compact 1 was placed in a sintering furnace, and the temperature inside the furnace was raised to 800°C at a heating rate of 300°C / h in a 100% oxygen atmosphere. After reaching 800°C, the temperature was maintained at 800±2°C for 2.5 hours. After 2.5 hours had elapsed, heating was stopped and the furnace was left to stand until the temperature inside the furnace dropped to 50°C or below, yielding LiMO-4.

[0141] Example 5 The powder compact 3 was placed in a sintering furnace, and the temperature inside the furnace was increased to 800°C at a heating rate of 300°C / h under a 100% oxygen atmosphere. After reaching 800°C, the temperature was maintained at 800±2°C for 2.5 hours. After 2.5 hours, heating was stopped and the furnace was left to stand until the temperature inside the furnace dropped to 50°C or below, thereby obtaining LiMO-5.

[0142] Comparative Example 1 Mixture 2 was filled into the powder molding die, and a pressure of 20 MPa was applied to the die using the uniaxial press to obtain a cylindrical green compact C1 with a diameter of 15 mm and a height of 20 mm. The same procedure as in Example 1 was followed except that green compact C1 was used instead of green compact 1, to produce LiMO-C1. Green compact C1 was self-supporting. No peak was observed in the range of 2θ=44.6±2° for green compact C1, and the L 104 could not be calculated.

[0143] Comparative Example 2 LiMO-C2 was produced in the same manner as in Example 1, except that Powder 1 was sintered as it was without being compacted.

[0144] Comparative Example 3 Lithium hydroxide was weighed out so that the amount (molar ratio) of Li was 1.14 relative to the total amount of Ni, Co, and Mn contained in MCC-1, which was 1. MCC-1 and lithium hydroxide were mixed to obtain a mixture C3.

[0145] The mixture C3 was kept in a sintering furnace under a 100% oxygen atmosphere at 650°C for 5 hours to obtain a powder C3 containing a reactant. The powder 3 was filled into the powder molding die, and a pressure of 20 MPa was applied to the die at room temperature using the uniaxial press to obtain a cylindrical green compact C3 with a diameter of 15 mm and a height of 13 mm. LiMO-C3 was obtained in the same manner as in Example 1. When the composition of the powder C3 was analyzed, it was found that in formula (1), a = 0.14, x = 0.15, and y = 0, and the element M1 was Mn and Co. In addition, the X-ray diffraction measurement showed that the powder C3 had a layered rock salt structure. The green compact C3 was self-supporting.

[0146] Comparative Example 4 LiMO-C4 was obtained in the same manner as in Example 1, except that Powder 2 was filled into the powder molding die, and a pressure of 100 MPa was applied to the die using the uniaxial press to obtain a cylindrical green compact C4 having a diameter of 15 mm and a height of 13 mm. The green compact C4 was self-supporting.

[0147] Comparative Example 5 LiMO-C5 was obtained in the same manner as in Example 1, except that Powder 2 was filled into the powder molding die, and a pressure of 200 MPa was applied to the die using the uniaxial press to obtain a cylindrical green compact C5 having a diameter of 15 mm and a height of 13 mm. Green compact C5 was self-supporting.

[0148] Comparative Example 6 Lithium hydroxide was weighed out so that the amount (molar ratio) of Li was 0.99 relative to the total amount of Ni, Co, and Mn contained in MCC-1, which was 1. MCC-1 and lithium hydroxide were mixed to obtain a mixture C6.

[0149] The mixture C6 was kept in a sintering furnace under a 100% oxygen atmosphere at 650°C for 5 hours to obtain a powder C6 containing a reactant. A compact C6 and LiMO-C6 were obtained in the same procedure as in Example 1, except that the powder C6 was used. A composition analysis of the powder C6 showed that in formula (1), a = -0.01, x = 0.15, and y = 0, and the element M1 was Mn and Co. In addition, the X-ray diffraction measurement showed that the powder C6 had a layered rock salt structure. The compact C6 quickly became powdery and did not stand on its own. Therefore, the density could not be measured.

[0150] In Examples 1 to 5 and Comparative Examples 1 to 6, the powder Li / (M1+M2), particle strength S / pressure P, holding time at the highest holding temperature during sintering of the green compact (referred to as "holding time" in the table), green compact density, half-width A, L 003 / L 104 , the ratio of LiOH contained in the powder to the total mass of the powder (referred to as "LiOH ratio" in the table), and the ratio of Li to the total mass of the powder 2 CO 3 Percentage of (in the table, "Li 2 CO 3 The compactability and crushability of the powder, the L of LiMO 003 (In the table, "LiMO's 003 Table 1 shows the amount of LiMO in the CAM, the proportion of the rock salt structure relative to the entire LiMO crystal (referred to as "proportion of rock salt structure" in the table), and the presence or absence of fine particles contained in LiMO (referred to as "presence or absence of fine particles" in the table), as well as the initial discharge capacity of the lithium secondary batteries produced using LiMO as the CAM in Example 1, Examples 3 to 5, and Comparative Example 2. Although not shown in the table, the Li / (M1+M2) value of the green compact is the same as the Li / (M1+M2) value of the powder.

[0151] [Table 1]

[0152] From the above results, Examples 1 to 5 are L 003 It was found that LiMO with a large value, a rock salt structure ratio of 0.8 vol.% or less, and no fine particles were observed was obtained.

[0153] In Comparative Example 1, pressure was applied to the mixture before sintering to obtain a green compact. Therefore, all of the LiOH contained in the mixture is LiOH derived from the raw materials, and the proportion of LiOH is significantly higher than in the powders of the other Examples and Comparative Examples. 2 CO 3 In the method described in "Ratio of LiOH and LiCO 3 In Comparative Example 1, LiMO was produced using a green compact obtained by applying pressure to a mixture and having an S / P and a half-width A outside the range of the present invention. The LiMO obtained was 003 The value of LiMO was small, and fine particles were confirmed. 003 The value of was decreased. The LiMO of Comparative Example 3 obtained using a green compact with Li / (M1+M2) of 1.14 had poor crushability and fine particles were confirmed. In Comparative Examples 4 and 5, the experiment was carried out under conditions where S / P was outside the range of the present invention, and LiMO was produced using a green compact with a density outside the range of the present invention. Fine particles were confirmed in the obtained LiMO. In Comparative Example 6, where Li / (M1+M2) was 0.99, the compact had low moldability. Therefore, the other LiMOs were not evaluated.

[0154] From the comparison of Examples 1 and 3 to 5, it can be seen that even if the holding time of the maximum temperature during sintering of the compact is extended, the L 003 It can be seen that the value of is large, the rock salt structure ratio is maintained at 0.8 volume % or less, and the initial discharge capacity value is also high. From these results, it was confirmed that according to the present invention, LiMO that maintains high crystallinity even under long-term sintering, has a small rock salt structure ratio, and has a high initial discharge capacity can be obtained. [Industrial Applicability]

[0155] According to the present invention, it is possible to provide a method for producing LiMO with high production efficiency, which can obtain LiMO with few fine particles and high crystallinity, and a green compact that can be used in this production method. [Explanation of symbols]

[0156] Reference Signs List 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery< / cam> < / limo>

Claims

1. A step of applying a pressure P [MPa] to a powder containing a reaction product of a lithium compound and a metal composite compound to obtain a green compact; and sintering the powder compact to obtain a lithium metal composite oxide. The ratio of the amount of Li to the total amount of metal elements other than Li contained in the powder is 1.00 or more and less than 1.14, A method for producing a lithium metal composite oxide, wherein a ratio S / P of the pressure P to a particle strength S [MPa] of the powder is 1.0 or more.

2. The density of the powder compact is 2.0 g / cm 3 3.0g / cm or more 3 The method for producing a lithium metal composite oxide according to claim 1 , wherein the temperature is less than 100° C.

3. The method for producing a lithium metal composite oxide according to claim 1 or 2, wherein the reactant has a layered rock salt structure.

4. 3. The method for producing a lithium metal composite oxide according to claim 1, wherein in an X-ray diffraction measurement of the compact using CuKα radiation, a half-value width of a peak present within a range of 2θ=18.7±2° is 0.50° or less.

5. The particle strength S is 50 MPa or more, The method for producing a lithium metal composite oxide according to claim 1 or 2, wherein the S / P is 1.4 or more.

6. LiOH and Li in the powder as determined by neutralization titration of the powder 2 CO 3 The method for producing a lithium metal composite oxide according to claim 1 or 2, wherein the proportions of are 0.60 mass % or more and 0.20 mass % or more, respectively, relative to the total mass of the powder.

7. The method for producing a lithium metal composite oxide according to claim 1 or 2, wherein the pressure P is 10 MPa or more and less than 100 MPa.

8. 3. The method for producing a lithium metal composite oxide according to claim 1, wherein in the step of obtaining the lithium metal composite oxide, the compact is fired at 700° C. or higher and 1000° C. or lower in an atmosphere having an oxygen ratio of 50% or higher.

9. The method for producing a lithium metal composite oxide according to claim 1 or 2, wherein the powder satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-x-y):x:y...(1) (In formula (1), 0≦a<0.14, 0≦x≦0.5, 0≦y≦0.5, and 0≦x+y<1; M1 is at least one element selected from the group consisting of Co, Mn, and Al; and M2 is at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.)

10. 3. The method for producing a lithium metal composite oxide according to claim 1, further comprising the step of mixing the lithium compound and the metal composite compound and firing the mixture to obtain the powder, prior to the step of obtaining the powder compact.

11. The method for producing a lithium metal composite oxide according to claim 10, wherein in the step of obtaining the powder, the lithium compound and the metal composite compound are fired at 300° C. or more and 700° C. or less in an atmosphere having an oxygen ratio of 50% or more.

12. 3. The method for producing a lithium metal composite oxide according to claim 1, wherein the powder compact is a molded body that is self-supporting without any external force other than gravity.

13. A compact containing a reaction product of a lithium compound and a metal composite compound, a substance amount ratio of Li to a total amount of metal elements other than Li contained in the powder compact is 1.00 or more and less than 1.14; The density of the powder compact is 2.0 g / cm 3 3.0g / cm or more 3 is less than A powder compact, in which, in an X-ray diffraction measurement of the powder compact using CuKα rays, the half-value width of a peak existing within a range of 2θ=18.7±2° is 0.50° or less.

14. In the X-ray diffraction measurement, the crystallite size L of the peak present in the range of 2θ=18.7±2° 003 and the crystallite size L of the peak present in the range of 2θ = 44.6 ± 2° 104 Relative to L 003 / L 104 The powder compact according to claim 13, wherein the σ is 1.2 or less.

15. The powder compact according to claim 13 or 14, wherein the powder compact satisfies the following formula (1): Li:Ni:M1:M2=(1+a):(1-x-y):x:y...(1) (In formula (1), 0≦a<0.14, 0≦x≦0.5, 0≦y≦0.5, and 0≦x+y<1; M1 is at least one selected from the group consisting of Co, Mn, and Al; and M2 is at least one selected from the group consisting of Fe, Cu, Ti, Mg, Ca, Zn, Sn, Zr, B, Si, Nb, W, Ta, Ba, S, and P.)

Citation Information

Patent Citations

  • Manufacturing method for positive electrode active material for non-aqueous electrolyte secondary battery, and molded body

    JP2019175694A